The Role of Trust as Mediator in the Effect of Religiosity and Bank Image towards Consumers’ Intention: : An Empirical Case Study of Bank Muamalat, Indonesia. - Rizal Ula Ananta Fauzi; Dian Cita Ningtiyas Ari Kadi; Arman Hj. Ahmad (Asia Pacific Journal of Social Science Research, 2021)
The existence of banking in Indonesia is getting more advanced with the increasing use of society for banking services. In addition to conventional banks, Islamic banks are starting to become the choice of predominantly Muslim Indonesians. However, the phenomenon occurs with the Muamalat bank, a pure bank established in sharia, experiencing a decrease in the public's Intention to make financing. This creates a study to conduct research, so that research is needed to determine the factors that influence people's Intention to make financing at Muamalat Bank. This research method uses quantitative research using SmartPLs analysis with a sample of 220 respondents. From the study results, it is found that Religiosity affects consumer trust and Intention. The bank's image affects public Trust and does not influence the public's Intention to make financing. Henceforth, Trust can mediate Religiosity and corporate image on the public's Intention to make financing at the Muamalat bank. This result can take into consideration the Muamalat bank's decision to take a marketing policy.